War of Attrition and Power of Inaction: The Spanish Financial Crisis and its Lessons for the European Banking Union - Miguel Otero-Iglesias; Sebastián Royo; Federico Steinberg Wechsler (Revista de Economía Mundial, 2017)
The aim of this paper is to analyse the main causes of the Spanish financial crisis (2009-12). Risk mismanagement in the saving banks was the main culprit but the intensity of the crisis was due to the “war of attrition” between the main stakeholders, which was further reinforced by the “power of inaction” of the big Spanish banks. Ultimately, only European institutions resolved the stalemate. Three lessons can be extracted for the European Banking Union: 1) regulators need to be able to confront the prevalent zeitgeist and vested interests; 2) regionally-decentralised supervision can lead to problems. Small banks can create havoc; 3) the Eurozone will need a bigger fiscal backstop to deal with future systemic banking crises.